Pathogenic Protozoans of Grasshopper from Imphal, Manipur, India - N. Mohilal, Indira Yumnam,; Shah, M. Manjur (Journal of Experimental Sciences, 2019)
Septate gregarines or Cephaline gregarines are a group of parasitic protozoans of Grasshopper. Eugregarines are the most common; these species inhabit the midgut though rarely pathogenic in the mid-gut, they have been reported to block the gut of the host. Those inhabiting the gastric caeca cause serious pathologies than the midgut-inhabiting species. Some of the best known genera found in Manipur are Gregarina, Phleobum, Didymophyes, Amphiplatyspora, Lepismatophila, Quadruspinospora and Quadruknobspora. The study reports the morphological details of 16species of the above genera collected from Imphal. Illustrative diagrams and photomicrographs are provided for better species identification.